Deixis and Pronouns in Romance Languages. - Kragh, Kirsten Jeppesen (Studies in language companion series., 2013)
With an analytical framework based upon Émile Benveniste's theory on deixis and pronouns and Laura Vanelli's theory on determiners, I discuss how Francesco Soave (1743-1806) in his grammar Gramatica ragionata della lingua italiana (1771) deals with personal pronouns and demonstratives. As regards personal pronouns, I conclude that Soave, in a short form, basically expresses the same view as Benveniste. As regards the demonstratives I conclude that Soave's analysis, though presenting the formal system in a classical way, combines original intralinguistic and extralinguistic explanations.